Estudo da espessura da regressão como fator prognóstico nos melanomas cutâneos finos - Pataleão, Luciana (2007)
Background: In the last few decades, thin melanomas have been more frequently diagnosed, due to new early detection techniques and public awareness campaigns. These lesions were regarded as excellent prognosis, with 90% of survival in 10 years. However, in the last few years, thin melanomas with recurrency or metastases have been reported, some with lethal course. Many clinical and histological variables have been studied, but none of them, until now, could explain these thin melanomas with bad outcoming. Regression has been studied as a possible factor associated to worst prognosis. Objective: To correlate the regression thickness of thin melanomas (= 1,00mm) with disease free survival time. Materials and method: We studied 84 thin melanomas diagnosed between 1990 and 2000 at the Hospital Universitário Antônio Pedro (Niterói RJ) and at Instituto Nacional do Cancer at Rio de Janeiro. The cases with available paraffin block were submitted to elastic fibers technique (Weigert) for better measuremet of regression thickness; immunohistochemistry with anti-Melan A antibody was performed to locate the deepest tumoral cell. Kang et al. (1993) criteria for regression recognition and classification (early, intermediate, late) was used. Results: Weigert technique was better than H&E to measure the thickness of regression. The use of the AEC chromogen made it easier to identify the melanocytes among the melanophages of the regression area. More incidence was observed in women (48 patients). Superficial spreading (SSM) predominated (65 cases); 28 cases were Clark s invasion level I; 26 (II); 24 (III); 6 (IV) and none Clark V. Regression (in any phase) was observed in 70 of 84 thin melanomas (83,3%), and 30 cases (35,7%) showed late regression, reported by authors as the greatest prognostic impact. Regression thickness ranged from 0,16 to 1,53mm, 67,2% below 0,76mm, 21,4% from 0,76 to 1,0mm and 11,4% above 1,0mm. Disease free survival time ranged from 17 days to 108 months. Five cases (5,9%) had bad outcoming: two were in situ melanomas with late regression and developed local recurrency; one corresponded to in situ melanoma with no regression, that showed local recurrency and regional metastases; one Clark s level IV with intermediate regression and with regional metastases and one Clark s level III with intermediate regression who developed disseminated metastases and death. Conclusions: There was no estatistic correlation between regression and disease free survival time (p > 0,05), being of great relevance that only five cases from the sample had bad outcoming, four of which showed regression. Sample must be enlarged, in order to compare patients presenting thin melanoma with bad outcoming and equivalent group with good outcoming